2011
DOI: 10.4028/www.scientific.net/amm.110-116.1374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quenching Media and Ageing Time on Al6061-Beryl Composites

Abstract: — Aluminum alloy based metal matrix composites are becoming very popular because of their outstanding properties such as high strength to weight ratio, excellent mechanical properties and improved wear properties. From literature survey it was observed that very limited report available on Aluminum alloy-beryl composites, particularly on the effect of beryl content, quenching media and heat treatment on the mechanical and wear properties of Aluminum-beryl composites. Accordingly, the aims of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…The wear resistance decreases as the sliding distance increases for the ascast and solutionized alloy and its composites. A similar trend was also observed independently for different sliding distances, applied loads and sliding velocities (Howell & Ball, 1995;Reddappa et al, 2011;Skolianos & Kattamis, 1993;Suresh et al, 2002;Venkataraman & Sundararajan, 1996;Wu & Li, 2000). Figure 6.…”
Section: Hardnesssupporting
confidence: 81%
See 1 more Smart Citation
“…The wear resistance decreases as the sliding distance increases for the ascast and solutionized alloy and its composites. A similar trend was also observed independently for different sliding distances, applied loads and sliding velocities (Howell & Ball, 1995;Reddappa et al, 2011;Skolianos & Kattamis, 1993;Suresh et al, 2002;Venkataraman & Sundararajan, 1996;Wu & Li, 2000). Figure 6.…”
Section: Hardnesssupporting
confidence: 81%
“…Al2024-Beryl composites were developed by adding a proportionate weight percentage of reinforcement from 0 wt.% to 10 wt.% in steps of 2 wt.%. This liquid metallurgy route has been used for developing MMCs by many researchers (Basavarajappa & Chandramohan, 2005;Krishnan, 1980;Ramesh, Swamy, & Chandrashekar, 2011;Ramesh, Bharathesh, Verma, & Keshavamurthy, 2012;Reddappa, Suresh, Niranjan, & Satyanarayana, 2011;Skolianos & Kattamis, 1993;Suresh et al, 2003;Xu & Chung, 1988) because this method is the most economic for the fabrication of MMCs. The castings were tested to determine common casting defects using an ultrasonic flaw detector.…”
Section: Development Of Compositesmentioning
confidence: 99%
“…The chance of debonding of nano particles due to the incessant sliding causes the particles to get slackened from the matrix material and get stuck among the sliding surfaces, whereas it might act like an abrader leading to a short period of wear. Generally, this is the cause for enhanced wear rate [37,38]. The Energy Dispersive Spectroscopy study of nano particles reinforced composite is shown in Fig.…”
Section: Microstructural Observationsmentioning
confidence: 99%
“…Strengthening of Al composite with strong discontinuous SiC fibers is confirmed by Arsenault and Fischer [35], Arsenault [36] and Taya et al [37]. Reddappa et al [38] studied the effect of quenching on Al6061 composite with increasing beryl addition (2-12 wt.%) and found improved hardness and strength in heat treated and aged samples. Beryl particle additions have given rise to large residual compressive stress developed during solidification due to difference in coefficient of expansion between ductile matrix and brittle ceramic particles.…”
Section: Introductionmentioning
confidence: 88%